A reappraisal of the sinus venosus defect. (28th January 2022) - Chowdhury, Ujjwal Kumar; Anderson, Robert H; Pandey, Niraj Nirmal; Sharma, Srikant; Sankhyan, Lakshmi Kumari; George, Niwin; Goja, Shikha; Arvind, Balaji
Abstract: OBJECTIVES: The phenotypic features and morphogenesis of the 'sinus venosus defect' remain controversial. The phenotypic features are anomalous systemic connections of 1 or more pulmonary veins that retain their left atrial connection, usually associated with a biatrial connection of the superior caval vein. Cases with these features, however, have not always been described as sinus venosus defects. METHODS: We reviewed the findings documented in the literature from 11 patients with a biatrial connection of the superior caval vein, most reported following an autopsy examination. We compared these findings with the anatomical details of 50 patients undergoing surgical correction in our centre, paying particular attention to the override of the superior caval vein. RESULTS: In only two-thirds of those undergoing surgery did the superior caval vein override the rims of the oval fossa, with the degree of override >50% in only 2 individuals. It is only these latter 2 cases that are directly comparable to the reported cases of biatrial connection of the superior caval vein. CONCLUSIONS: Our comparisons provide new insights into the developmental background and phenotypic features of the superior sinus venosus defect. The defects exist because of the anomalous systemic connection of the pulmonary veins that retain their left atrial connections but not always in association with a biatrial connection of the superior caval vein. In extreme cases, nonetheless, they can underscore the connection of the caval vein to the morphologically left atrium, frequently described previously as a 'biatrial connection'. The sinus venosus defect is better considered a venovenous malformation than a septal defect. Abstract : The term 'sinus venosus defect', as far as we can establish, did not enter the lexicon of congenital cardiac malformations until Ross described a case in this fashion in 1956 [1].